2013
DOI: 10.4028/www.scientific.net/msf.755.39
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Weld Bead Parameters of Overlay Deposited on D2 Steel Components by Plasma Transferred Arc (PTA) Process

Abstract: Plasma Transferred Arc (PTA) process is increasingly used in applications where enhancement of wear, corrosion and heat resistance of metals surface is required. The shape of weld bead geometry affected by the PTA welding process parameters is an indication of the quality of the weld. PTA is a versatile method of depositing high-quality metallurgically fused deposits on relatively low cost surfaces. The overlay deposited is an alloy that is hard and more corrosion resistant than counterparts laid down by Gas T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…6 shows the results of the wear test, in this plot can be appreciated the lost volume and the specific ratio. Compared with D2 steel filler metal applied in D2 steel substrate, Ni base filler metal NiCrBSi presented a wear coefficient k lower, and therefore the wear resistance on the surface is improved significantly [13]. This behavior is due to the homogeneous carbide precipitation zone.…”
Section: Resultsmentioning
confidence: 92%
“…6 shows the results of the wear test, in this plot can be appreciated the lost volume and the specific ratio. Compared with D2 steel filler metal applied in D2 steel substrate, Ni base filler metal NiCrBSi presented a wear coefficient k lower, and therefore the wear resistance on the surface is improved significantly [13]. This behavior is due to the homogeneous carbide precipitation zone.…”
Section: Resultsmentioning
confidence: 92%
“…At the same time cost of the base material is comparatively low, which makes it suitable for the manufacturing of very heavily loaded parts used in the machinery. 25 The base material is the metal on which the deposition of other material, having desired mechanical properties, is to be deposited to enhance the surface conditions of the overall component. It is very evident from various literature that plain carbon steel and alloy steel are normally used to manufacture the structural parts of the equipment.…”
Section: Hardfacing Materialsmentioning
confidence: 99%
“…At the same time cost of the base material is comparatively low, which makes it suitable for the manufacturing of very heavily loaded parts used in the machinery. 25…”
Section: Hardfacing Materialsmentioning
confidence: 99%
“…Weld bead is an important geometric parameter able to define the properties of the hardfaced layer: several studies demonstrated that there is a close relation between the weld bead shape and the quality of the layer [19][20][21]. Considering the different type of equipment, powder mixtures and process parameters, many combinations of the specifications could be used to find an appropriate welding procedure.…”
Section: Metallurgical Characterization Of a Weld Bead Coatingmentioning
confidence: 99%